Membrane Fouling Potential of Secondary Effluent Organic Matter (EfOM) from Conventional Activated Sludge Process - Wei, Chun-Hai; Amy, Gary (Journal of Membrane and Separation Technology, 2012)
Secondary effluent organic matter (EfOM) from a conventional activated sludge process was filtered through constant-pressure dead-end filtration tests with a sequential ultrafiltration (UF, molecular weight cut-off (MWCO) of 10k Dalton) and nanofiltration (NF, MWCO of 200 Dalton) array to investigate its membrane fouling potential. Advanced analytical methods including liquid chromatography with online carbon detection (LC-OCD) and fluorescent excitation-emission matrix (F-EEM) were employed for EfOM characterization. EfOM consisted of humic substances and building blocks, low molecular weight (LMW) neutrals, biopolymers (mainly proteins) and hydrophobic organics according to the sequence of their organic carbon fractions. The UF rejected only biopolymers and the NF rejected most humics and building blocks and a significant part of LMW neutrals. Simultaneous occurrence of cake layer and standard blocking during the filtration process of both UF and NF was identified according to constant-pressure filtration equations, which was possibly caused by the heterogeneous nature of EfOM with a wide MW distribution (several ten to several million Dalton). Thus the corresponding two fouling indices (kc for cake layer and ks for standard blocking) from UF and NF could characterize the fouling potential of macromolecular biopolymers and low to intermediate MW organics (including humics, building blocks, LMW neutrals), respectively. Compared with macromolecular biopolymers, low to intermediate MW organics exhibited a much higher fouling potential due to their lower molecular weight and higher concentration.